1998
DOI: 10.1046/j.1537-2995.1998.38298193096.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodilution and intravenous perflubron emulsion as an alternative to blood transfusion: effects on tissue oxygenation during profound hemodilution in anesthetized dogs

Abstract: Bolus intravenous administration of 60-percent (wt/vol) perflubron emulsion and further hemodilution from a Hb of 7 g per dL to one of 3 g per dL were as effective as autologous RBC transfusion in maintaining tissue oxygenation during volume-compensated blood loss designed to mimic surgical bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
52
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 16 publications
0
52
0
5
Order By: Relevance
“…To date, this latter phase remains firmly within the purvey of blood transfusion medicine; however, alternative oxygen-carrying volume fluids such as modified hemoglobins (Hbs) and fluorocarbons have emerged in the past decade. Few of these materials have been objectively analyzed in terms of their transport properties at the level of the microscopic blood vessels, where the actual exchange of oxygen takes place, to determine if their properties lead to adequate transport processes at the cellular/tissue level (8).…”
mentioning
confidence: 99%
“…To date, this latter phase remains firmly within the purvey of blood transfusion medicine; however, alternative oxygen-carrying volume fluids such as modified hemoglobins (Hbs) and fluorocarbons have emerged in the past decade. Few of these materials have been objectively analyzed in terms of their transport properties at the level of the microscopic blood vessels, where the actual exchange of oxygen takes place, to determine if their properties lead to adequate transport processes at the cellular/tissue level (8).…”
mentioning
confidence: 99%
“…In particular, a reduction of Hb crit could be achieved by hypothermia (moderate reduction of body core temperature reduces total body O 2 demand [18]), infusion of norepinephrine (stabilization of CPP during hemodilution [19]), infusion of artificial O 2 carriers (maintenance of CaO 2 despite reduced hematocrit [20,21]) and continuous NMB (lowering skeletal muscular O 2 demand [22]). …”
Section: Discussionmentioning
confidence: 99%
“…In several experimental studies, a decrease in Hb crit demonstrated that anemia tolerance is increased by (1) hypothermia (moderate reduction of body core temperature reduces total body O 2 demand [16]), (2) hyperoxic ventilation (bioavailability of physically dissolved O 2 is excellent in profound anemia [12,17,18]), (3) infusion of norepinephrine (stabilization of coronary perfusion pressure during hemodilution [13]), and (4) artificial O 2 carriers (maintenance of CaO 2 despite reduced hematocrit [19,20]). In contrast, anemia tolerance is decreased by (1) hypovolemia (reduction of microcirculatory O 2 supply), (2) profound anesthesia (pharmacologic reduction of the cardiac output response to hemodilution [21,22]) and (3) by coronary artery disease (reduced coronary flow reserve [23]).…”
Section: Discussionmentioning
confidence: 99%